International Food Information Service (IFIS) - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
International Food Information Service (IFIS)IFIS is a specialist database producer. Its purpose is to advance public education, training, research and development in the field of food science and technology through its main database Food Science...